The perceptions of student counsultants towards The Inital Assessment and Consultation (IAC) model of assessment. - Warburton, Bianca (My University, 2010)
In 1982, a new model of psycho-educational assessment, called the Initial Assessment and Consultation Approach (IAC), was introduced into the Education Clinic of the Division of Specialised Education at the University of the Witwatersrand (WITS). It has continued to be used in the new Emthonjeni Centre at WITS University. The IAC assessment model was developed in response to criticisms and limitations of existing assessment practices. It represents an approach that is client oriented, in that it encourages consultants and clients to arrive together at their own decisions. Key to the model is a joint problem-solving approach, where the concept of the client’s control, consent and commitment are imperative. The aim of this study was to explore student consultants’ perceptions of the IAC model of assessment. More specifically, the study explored the perceptions of the effectiveness of the IAC as a tool for psycho-educational assessment; the student consultants’ opinion regarding the model and lastly past students’ use of the IAC approach at internship sites or places of work. The results of the study were qualitatively examined through the use of thematic content analysis, which provided rich description participants’ opinions. The sample consisted of forty respondents. Information letters were distributed to all participants and data was gathered through the use of an online questionnaire. The questionnaire was structured specifically to elicit the participants’ perceptions of the IAC model of psycho-educational assessment. The results indicate that the IAC is perceived as an effective approach to psycho-educational assessment, by student consultants at WITS University, and many of the principles of the approach are continued to be adopted by past students at their internship sites or places of work.
Keywords: Psycho-educational assessment; Initial Assessment and Consultation Approach (IAC); Models of assessment; Student consultants; Client families; Assessment in the South African context